The Role of Community-Based Organizations in Adolescent Sexual Health Promotion - Fisher, Christopher; Reece, M.; Wright, E.; Dodge, B.; Sherwood-Laughlin, C.; Baldwin, K. (Sage Publications, Inc., 2012)
Many scholars and practitioners have advocated for a more ecological approach to sexual health promotion for adolescents, such as one that includes involvement from schools, parents, and community organizations. Although extensive research has been conducted with schools and parents, little is known about the roles community-based organizations (CBOs) may play in the education and promotion of sexual health to young people. This study aimed to (a) identify the types of sexual health and sexuality-related questions asked by youth and programming/services, resources, and referrals currently being provided by CBOs; (b) explore the approaches used by CBOs when developing and implementing sexual health promotion programs; and (c) compare these findings with those from a similar study on school teachers, counselors, and nurses within the same state. Data collected from 169 people working in CBOs indicate that a wide variety of topics were covered by CBOs through programming and services, resources, and/or referral protocols. Topics covered varied in frequency. Overall, participants indicated a relatively comprehensive and accessible approach to providing sexuality information to youth. The results of this study suggest that CBOs should be included in the range of sources to be used for comprehensive sexual health promotion. If such organizations are supported with information, training, and resources, they could play a valuable role in the promotion of sexual health for adolescents.